If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = 6x + 5 Reorder the terms: 1 + 5x = 6x + 5 Reorder the terms: 1 + 5x = 5 + 6x Solving 1 + 5x = 5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1 + 5x + -6x = 5 + 6x + -6x Combine like terms: 5x + -6x = -1x 1 + -1x = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + -1x = 5 + 0 1 + -1x = 5 Add '-1' to each side of the equation. 1 + -1 + -1x = 5 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 5 + -1 -1x = 5 + -1 Combine like terms: 5 + -1 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 2(x-3)-7=6-5(x+1) | | x^2-6x+y^2+2y+44=y | | 4a+8=5a-5 | | 17y-5y^2-12=0 | | 2s+7=4s-15 | | -2a+7=a-87a | | y^2-6*y+7=0 | | 4k^2+18k-18=0 | | y=-0.0741x^2 | | 2k^2+9k-9=0 | | 76+4x= | | 10m^5/3 | | 2x^2+y^2-x-2y+6=0 | | 5555=555 | | Xy+xz=6 | | (5*2x)+(7*3x)=260000 | | 18x+14y=4314 | | Solve(x+1)(x+2)(x+3)(x+5)=144 | | 4t+17=5 | | 3(5t-3)+(4t-8)= | | 5z+2+4z=85 | | 7(4+U)= | | g(x)=af(x+b) | | (2x+5)(3x-5)=90 | | 9x=78x | | (11+4)14=49 | | (3+4)14=49 | | (2+4)14=49 | | 48400(100-10)(100-10)=32400(100+10)(100+10) | | (7+4)14=49 | | 0.72x+1.5+3x=2x+9 | | 48400(100-x)(100-x)=32400(100+x)(100+x) |